Emergence of ocular toxicities associated with novel anticancer therapeutics: What the oncologist needs to know. (April 2022) - Ali, Azka; Shah, Ankit A.; Jeang, Lauren J.; Fallgatter, Kyle S.; George, Thomas J.; DeRemer, David L.
Highlights: With rapid approval of targeted anti-cancer agents, it is even more pertinent for oncologists to be aware of the novel adverse events. While targeted agents have less off-target toxicity, there is notable overlapping toxicity in several organs, including the eye, due to expression of the common receptors. In this review, we present a succinct, yet updated clinical overview of ocular adverse events related to select small molecule inhibitors, monoclonal antibodies, and antibody drug conjugates. We also provide guidance on in-clinic management for mild events as well as recommendations on referral to ophthalmology for expert opinion for severe cases. Abstract: As cancer treatment evolves in the era of precision oncology, molecularly targeted agents (MTAs) have become frontline therapy for many cancers. MTAs are biologically targeted and thought to have less off-target toxicity; however, the eye is particularly susceptible to off-target toxicities given its unique microenvironment. In this review, we present commonly used FDA-approved MTAs, any associated ocular toxicities and review the mechanisms, frequency, severity, and management. Increased awareness and communication between clinicians caring for cancer patients is needed for individualized risk assessment, earlier diagnosis, and mitigation of ocular toxicities.